Intraocular pressure control after trabeculectomy in the patients with primary open angle glaucoma and pseudoexfoliative glaucoma followed up for 3 to 5 years - Marić, Vesna; Marković, Vujica; Božić, Marija; Marjanović, Ivan; Hentova Senćanić, Paraskeva; Kontić, Djordje (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Trabeculectomy is a safe procedure which effectively reduces the intraocular pressure (IOP). IOP is the most frequent indicator of success after glaucoma surgery. The aim of this work was to evaluate the long-term pressure control in primary open-angle glaucoma (POAG) and in pseudoexfoliative glaucoma (XFG) after primary trabeculectomy without the use of mitomycin-C (MMC), 3 to 5 years after trabeculectomy. Methods. This study involved a retrospective evaluation of 332 consecutive patients (352 eyes), 174 patients (188 eyes) with POAG (mean age of 64.0 ± 8.6 years) and 158 patients (164 eyes) with XFG (mean age of 70.7 ± 8.9 years) who underwent primary trabeculectomy between January 2007 and December 2009 at the Clinic for Eye Diseases, Clinical Center of Serbia in Belgrade. A successful control of IOP was defined as achieving IOP ≤ 21 mmHg without medication (complete success), or with a single topical medication (qualified success). Results. According to the type of glaucoma POAG/XFG preoperative IOP was 28.4 ± 6.3/30.4 ± 8.4 mmHg, respectively (p = 0.311) and last postoperative IOP was 16.9 ± 5.2/18.7 ± 5.9 mmHg, respectively (p = 0.681). According to the Kaplan-Meier survival curve, the complete success in the group with POAG in 1, 3 and 5 years were 85%, 75% and 58% and in the group with XFG were 82%, 70% and 56%, respectively. There was no statistically significant difference in the complete success rates between the patients with POAG and XFG. Conclusion. The primary goal of surgery was to achieve a sufficiently low IOP without additional medication, thus preventing progression of glaucomatous damage. In our study, the complete success in the group with POAG was achieved in 75% and 58% of the patientsin the period of 3 and 5 years after surgery, respectively and in the group with XFG complete success was achieved in 70% and 56% of the patients respectively.
Keywords: glaucoma open angle; exfoliation syndrome; trabeculectomy; intraocular pressure; treatment outcome